Teachers' Treatment of Students Who Smoke in the Classroom in the Perspective of Positive Law and Sharia Law: (Case Study of Teacher Slapping Student Who Smokes) - Windy Anastasya; Nurman Ritonga; Wahyuni Firnanda; Putri Ayu Regita; Rintan Gustia; Nurhabibah Pohan; Pinkan Azhara (Yayasan Multidimensi Kreatif, 2025)
Smoking among students is a violation of school rules that requires serious and thoughtful handling. Teachers, as educators, have the authority to impose sanctions on students who violate the rules, including those caught smoking on school grounds. However, in practice, the application of these sanctions often raises legal and ethical issues, particularly regarding child protection and human rights. This study aims to analyze the implementation of teacher sanctions against student smokers in schools from the perspective of positive law and Sharia law. The research method used is empirical research with a juridical-sociological approach. The results indicate that educational and proportional sanctions are generally in line with national legal provisions and Islamic Sharia principles. However, sanctions still have the potential to violate children's rights if not accompanied by a developmental approach. Therefore, clear guidelines are needed to ensure that the implementation of sanctions in schools remains within the law and Sharia values.